Rhetorics of Reflection: Revisiting Listening Rhetoric through Mindfulness, Empathy, and Non-violent Communication - Renea Frey (Journal of the Assembly for Expanded Perspectives on Learning, 2018)
Invention work with multiple perspectives and empathy set up the context for students to practice mindfulness as they develop skills in argumentative writing.